Osteology and phylogenetic affinities of the middle Eocene North American Bathornis grallator—one of the best represented, albeit least known Paleogene cariamiform birds (seriemas and allies). (16th June 2016) - Mayr, Gerald
Abstract: Bathornis (" Neocathartes ") grallator (Wetmore, 1944 ) from the middle Eocene of Wyoming is based on a partial skeleton, which is the most substantial record of the North American Bathornithidae and one of the most complete fossils of a Paleogene stem group representative of the Cariamiformes. So far, however, an assessment of the evolutionary significance of this important fossil has been hampered by the limited published osteological data. Moreover, cariamiform affinities of B . grallator and its true "genus"-level identity were recognized after the last comprehensive revision of the Bathornithidae, and some of its features were incorrectly portrayed in the original description. Here, the B . grallator holotype is restudied and the taxonomic composition and phylogenetic affinities of bathornithids are revised. It is suggested to restrict Bathornithidae to the taxon Bathornis, from which the putative bathornithid Paracrax differs in numerous features, with even cariamiform affinities of this latter taxon not having been established beyond doubt. B . grallator was a flightless bird and has recently been hypothesized to be the sister taxon of the likewise flightless South American Phorusrhacidae. The present analysis, however, supports a position outside a clade including Phorusrhacidae and Cariamidae (the cariamiform crown clade). Owing to their terrestrial way of living, Cariamiformes appear to have been prone to a loss of flight capabilities. B . grallator shows close similarities to a flightless cariamiform bird from the Paleogene of Europe, but the phylogenetic significance of this resemblance is difficult to assess owing to the limited material known of the latter species.